Utility of sonic hedgehog and keratin 8/18 immunohistochemistry for detecting ballooned hepatocytes. Issue 6 (29th March 2022) - Kusano, Hironori; Kondo, Reiichiro; Ogasawara, Sachiko; Omuraya, Minori; Okudaira, Masayuki; Mizuochi, Shinji; Mihara, Yutaro; Kinjo, Yoshinao; Yano, Yuta; Nakayama, Masamichi; Naito, Yoshiki; Akiba, Jun; et al.
Abstract : Aims: Ballooned hepatocytes represent liver cell degeneration and are histological hallmarks in the diagnosis of non‐alcoholic steatohepatitis, a severe form of non‐alcoholic fatty liver disease. However, the identification of ballooned hepatocytes is often difficult, especially in the clinical setting of patients with other chronic liver diseases. In this study, we investigated the utility of immunostaining for positive sonic hedgehog (SHh) protein and negative Keratin 8/18 (K8/18) expression on ballooned hepatocytes. Methods and results: Immunohistochemistry for SHh and K8/18 was evaluated independently by two experienced liver pathologists in non‐tumorous liver tissue from 100 cases of resected hepatocellular carcinoma of various aetiology. The degree of hepatocyte ballooning was scored as follows: 0, none; 1, few; 2, many ballooned hepatocytes. These evaluations were performed using routine haematoxylin and eosin (H&E) staining, followed by immunostaining for SHh or K8/18. Using SHh or K8/18 immunostaining combined with H&E staining, the score of ballooned hepatocytes was upgraded in 20 and 19 cases, and downgraded in none and 2 cases, respectively. The percentage of observed agreement for ballooned hepatocytes scoring was 85% and 92%, and the weighted kappa value was 0.806 and 0.893 with SHh or K8/18 immunohistochemistry. Considering the immunohistochemistry results, background liver disease diagnosis was changed in 15 out of 100 cases (15%) evaluated. Conclusions: SHh and K8/18 immunohistochemistry are useful in detecting ballooned hepatocytes, regardless of background liver disease, and improving pathological diagnosis accuracy. Abstract :